ChemR23 Dampens Lung Inflammation and Enhances Anti-viral Immunity in a Mouse Model of Acute Viral Pneumonia - Bondue, Benjamin (Public Library of Science, 2011)
Viral diseases of the respiratory tract, which include influenza pandemic, children acute bronchiolitis, and viral pneumonia of the elderly, represent major health problems. Plasmacytoid dendritic cells play an important role in anti-viral immunity, and these cells were recently shown to express ChemR23, the receptor for the chemoattractant protein chemerin, which is expressed by epithelial cells in the lung. Our aim was to determine the role played by the chemerin/ChemR23 system in the physiopathology of viral pneumonia, using the pneumonia virus of mice (PVM) as a model. Wild-type and ChemR23 knock-out mice were infected by PVM and followed for functional and inflammatory parameters. ChemR23(−/−) mice displayed higher mortality/morbidity, alteration of lung function, delayed viral clearance and increased neutrophilic infiltration. We demonstrated in these mice a lower recruitment of plasmacytoid dendritic cells and a reduction in type I interferon production. The role of plasmacytoid dendritic cells was further addressed by performing depletion and adoptive transfer experiments as well as by the generation of chimeric mice, demonstrating two opposite effects of the chemerin/ChemR23 system. First, the ChemR23-dependent recruitment of plasmacytoid dendritic cells contributes to adaptive immune responses and viral clearance, but also enhances the inflammatory response. Second, increased morbidity/mortality in ChemR23(−/−) mice is not due to defective plasmacytoid dendritic cells recruitment, but rather to the loss of an anti-inflammatory pathway involving ChemR23 expressed by non-leukocytic cells. The chemerin/ChemR23 system plays important roles in the physiopathology of viral pneumonia, and might therefore be considered as a therapeutic target for anti-viral and anti-inflammatory therapies.